1994
DOI: 10.3109/00365529409090464
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Term Follow-up after Treatment with Colloidal Bismuth Subcitrate and Tinidazole

Abstract: The connection between dyspeptic symptoms and Helicobacter pylori infection was studied prospectively in 21 children treated for verified H. pylori infection with bismuth subcitrate and tinidazole. Gastroscopy with biopsy was performed before and a mean of 4 months after discontinuation of the treatment. A second post-treatment check with determination of H. pylori antibodies and serum pepsinogen 1 level was made a mean of 1.5 years after cessation of treatment. The therapy given cleared the bacteria in 67% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 24 publications
1
39
0
Order By: Relevance
“…Overall, there is insufficient evidence to draw solid conclusions about health benefits from treating H. pylori infection in pediatric populations. Researchers conducting clinical trials aimed at assessing effects on children's health of eliminating H. pylori should design multicenter trials when needed for adequate numbers of subjects; such trials should include observational analysis to compare outcomes in 34 [15/44] Remained HP+ [11] 36 [4/11] HP negative at baseline [40] Percent with worsening reflux 12 [5/40] eliminated HP [44] 18 [8/44] Remained HP+ [11] 36 [4/11] HP negative at baseline [40] Mean decrease in severity score for epigastric pain Resolution of esophageal and gastric disease HP, H. pylori; ND, no data provided in report; +, positive; -, negative.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, there is insufficient evidence to draw solid conclusions about health benefits from treating H. pylori infection in pediatric populations. Researchers conducting clinical trials aimed at assessing effects on children's health of eliminating H. pylori should design multicenter trials when needed for adequate numbers of subjects; such trials should include observational analysis to compare outcomes in 34 [15/44] Remained HP+ [11] 36 [4/11] HP negative at baseline [40] Percent with worsening reflux 12 [5/40] eliminated HP [44] 18 [8/44] Remained HP+ [11] 36 [4/11] HP negative at baseline [40] Mean decrease in severity score for epigastric pain Resolution of esophageal and gastric disease HP, H. pylori; ND, no data provided in report; +, positive; -, negative.…”
Section: Resultsmentioning
confidence: 99%
“…In such cases, IgG antibody titers declined to normal levels or at least decreased by 50% at 6 months in the majority of children. If such a decrease was seen, endoscopy was not performed in the majority of cases, although Helicobacters were perhaps not totally eradicated in all cases (25). Upper gastrointestinal endoscopy is an invasive procedure performed under general anesthetic at our hospital and it was considered unethical to investigate children with no symptoms and in whom serum antibodies had declined to normal levels.…”
Section: Discussionmentioning
confidence: 95%
“…19 The present study also suggested that H. pylori eradication improved gastrointestinal symptoms in the infected children. While it remains controversial whether H. pylori infection is associated with gastrointestinal symptoms such as abdominal pain in children, 4,21,22 the Canadian Helicobacter Study Group 5 and the European Pediatric Task Force on Helicobacter pylori 23 have both recommended that H. pylori eradication therapy be considered if a child undergoes endoscopy and the infection is identified. Our data support these recommendations, but controlled trials will be needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 98%